Incorporating Comprehension Reading Strategies in Grade 4 English First Additional Language Classrooms: Challenges and Opportunities - Dube, Ntokozo Pallo; Mogale, Makobo Lydia (Studies in Learning and Teaching, 2025)
Reading comprehension is a foundational skill that is essential for learners’ academic achievement in the intermediate phase. However, Grade 4 learners in South Africa continue to face challenges in acquiring this skill, particularly because English is not their home language. This study aimed to explore the barriers and facilitators that Grade 4 English First Additional Language (FAL) teachers encounter when incorporating comprehension reading strategies into their instructional practices. Guided by Shulman’s theory of Pedagogical Content Knowledge (PCK), the study adopted a qualitative approach situated within the interpretivist paradigm. An exploratory case study design was used to gain in-depth insights from three Grade 4 English FAL teachers in the Motheo District, Free State Province. Data was generated through document analysis, classroom observations, and semi-structured interviews. Thematic analysis revealed that technological resources and teacher collaboration served as methods of effective comprehension instruction. In contrast, challenges such as limited pedagogical knowledge, curriculum misalignment, and persistent language barriers hindered the implementation of comprehension strategies. The study concludes that meaningful professional development, combined with improved alignment between curriculum content and reading pedagogy, is crucial for equipping teachers to support learners' reading comprehension effectively.